System Accuracy Evaluation of Four Systems for Self-Monitoring of Blood Glucose Following ISO 15197 Using a Glucose Oxidase and a Hexokinase-Based Comparison Method. (14th April 2015) - Link, Manuela; Schmid, Christina; Pleus, Stefan; Baumstark, Annette; Rittmeyer, Delia; Haug, Cornelia; Freckmann, Guido
Background: The standard ISO (International Organization for Standardization) 15197 is widely accepted for the accuracy evaluation of systems for self-monitoring of blood glucose (SMBG). Accuracy evaluation was performed for 4 SMBG systems (Accu-Chek® Aviva, Contour®XT, GlucoCheck XL, GlucoMen® LX PLUS) with 3 test strip lots each. To investigate a possible impact of the comparison method on system accuracy data, 2 different established methods were used. Methods: The evaluation was performed in a standardized manner following test procedures described in ISO 15197:2003 (section 7.3). System accuracy was assessed by applying ISO 15197:2003 and in addition ISO 15197:2013 criteria (section 6.3.3). For each system, comparison measurements were performed with a glucose oxidase (YSI 2300 STAT Plus™ glucose analyzer) and a hexokinase (cobas® c111) method. Results: All 4 systems fulfilled the accuracy requirements of ISO 15197:2003 with the tested lots. More stringent accuracy criteria of ISO 15197:2013 were fulfilled by 3 systems (Accu-Chek Aviva, ContourXT, GlucoMen LX PLUS) when compared to the manufacturer's comparison method and by 2 systems (Accu-Chek Aviva, ContourXT) when compared to the alternative comparison method. All systems showed lot-to-lot variability to a certain degree; 2 systems (Accu-Chek Aviva, ContourXT), however, showed only minimal differences in relative bias between the 3 evaluated lots. Conclusions: In this study, all 4 systems complied with the evaluated test strip lots with accuracy criteria of ISO 15197:2003. Applying ISO 15197:2013 accuracy limits, differences in the accuracy of the tested systems were observed, also demonstrating that the applied comparison method/system and the lot-to-lot variability can have a decisive influence on accuracy data obtained for a SMBG system.